Comparison Of the Post-Operative Pain and Vitality Status of Direct Pulp Capping Using Calcium Hydroxide and Biodentine in Deep Carious Permanent Teeth - Shah, Pir Jawad Ali; Rana, Muzammil Jamil Ahmed; Baig, Nasir Jamal; Akhter, Fahmeed; Aslam, Maha; Wahid, Maham (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the postoperative pain and symptoms after direct pulp capping with Calcium Hydroxide and Biodentine in a deep carious permanent tooth. Study Design: Prospective Comparative Study. Place and Duration of Study: Operative Department, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from Oct 2019 to Mar 2020. Methodology: Patients presenting to the OPD were considered for the study using randomized consecutive sampling. Patients ranging between 18 and 30 years, diagnosed with symptoms of reversible pulpitis, were divided into 2 groups, each with 31 participants. Group-A was given Calcium Hydroxide, while Group-B was administered Biodentine. Post-operative evaluation of pain was done after 24 hours, 3 days, and 7 days by visual analog scale, and the success rate was evaluated at 1 month, 3 months, and 6 months. Results: A total of 62 patients (31 in each group) were enrolled in this study. The mean age of the patients was 20.4±4.9 and 20.0±4.1 years. Calcium Hydroxide Group had 18 males (58.0%), and Biodentine Group had 20(64.5%). Similarly, in Calcium Hydroxide group, there were 13 females (42.0%), and in Biodentine Group, 11 females (35.5%). Comparison of visual analogue score between two groups, Calcium Hydroxide (Group-A) and Biodentine(Group-B) demonstrated as follows: on the first postoperative day, Calcium Hydroxide group revealed 18 patients (58.1%) had mild pain score (3-5), 12 patients (38.7%) reported ..... Conclusion: Biodentine results in less post-operative pain as compared to Calcium Hydroxide as a direct pulp capping agent.